(untitled) - Alley, Charles L. (New York, 1962)
Contents: Electron Ballistics; Semiconductors; Diodes; Basic Amplifiers; The Common Emitter Amplifiers; Multielectrode Tubes and Transistors; Small Signal Amplifiers; Amplifiers with Extended Frequency Range; Small Signal Tuned Amplifiers; Large Signal Amplifiers; Amplifiers with Negative Feedback; Large Signal Tuned Amplifiers; Oscilator Circuits; Amplitude Modulation and Detection; Frequency Modulation; Nonlinear Analysis; Power Supplies.
Keywords: Electronics,Điện tử